Arthroscopically Assisted Mini-Invasive Management of Perilunate Dislocations - Liu, Bo; Chen, Shan-Lin; Zhu, Jin; Wang, Zhi-Xin; Shen, Jie (Journal of Wrist Surgery, 2015)
Purpose The purpose of this study was to evaluate the outcomes of perilunate dislocations and fracture-dislocations treated with arthroscopically assisted mini-invasive reduction and fixation.Methods Between June 2012 and May 2014, 24 patients who had a dorsal perilunate dislocation or fracture-dislocation were treated with arthroscopically assisted reduction and percutaneous fixation. The mean follow-up was 14.8 months (range 6–32 months).Clinical outcomes were evaluated on the basis of range of motion; grip strength; Mayo Wrist Score; Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) questionnaire; and Patient-Rated Wrist Evaluation (PRWE) score. Radiographic evaluations included time to scaphoid union, carpal alignments, and any development of arthritis.Results The range of flexion-extension motion of the injured wrist averaged 86% of the values for the contralateral wrist. The grip strength of the injured wrist averaged 83% of the values for the contralateral wrists. The mean QuickDASH score was 6, and the mean PRWE score was 10. According to the Mayo Wrist Scores, overall functional outcomes were rated as excellent in 13 patients (54%), good in 6 (25%), fair in 4 (17%), and poor in 1 (4%). Scaphoid nonunion developed in one patient. Reduction obtained during the operation was maintained within normal ranges in all patients. Arthritis had not developed in any patient at final follow-up.Conclusions Arthroscopically assisted mini-invasive reduction with percutaneous fixation is a reliable and favorable alternative in the treatment of perilunate injuries according to our early follow-up results.Level of Evidence: Level IV, Therapeutic.
Keywords: perilunate dislocation; scaphoid fracture; minimally invasive surgery; wrist arthroscopy